Pengaruh Belief Adjustment dan Locus Of Control Terhadap Teknik Penganggaran Modal dan Pengambilan Keputusan Proyek - Stefannie Ekawaty (Jurnal Akuntansi Bisnis, 2012)
Significant capital investment decision-making within the company. Capital investment decisions to be taken include projects that are affected by capital budgeting techniques including DCF techniques, and non-financial non-DCF. Survey of capital budgeting techniques (Graham and Harvey, Kim et al., Klammer et al., Pike, Ryan and Ryan, Schall et al., In Chen, 2008) and Chen study (2008) using the contingency theory in the use of capital budgeting techniques the background of this research. The research was conducted with 85 participants experimented with techniques derived from the Auditing Practicum class. The results of this study is the belief adjustment and the LOC does not affect the capital budgeting techniques, but instead affect the project decision. Moreover, it also acquired the locus of control did not affect the relations of capital budgeting techniques in project decisions. So it can be concluded that the project decision-making, capital budgeting techniques used will influence the decision outcome